Dose Optimization of Aditoprim-Sulfamethoxazole Combinations Against Trueperella pyogenes From Patients With Clinical Endometritis by Using Semi-mechanistic PK/PD Model - Maan, Muhammad Kashif; Chaudhry, Tamoor Hamid; Sattar, Adeel; Shabbir, Muhammad Abu Bakr; Ahmed, Saeed; Mi, Kun; Ahmed, Waqas; Xie, Shuyu; Xin, Li; Huang, Lingli (Frontiers in Pharmacology, 2021)
Combinations of two and more drugs with different target sites are working as new treatment regimen for resistant clones of bacteria. Though, for a maximum effectiveness, combination of the drugs for optimal dosage regimen is challenging. In our study, we studied antimicrobial effect of aditoprim, a novel dihydrofolate reductase inhibitor and its synergistic effect with sulfamethoxazole. Synergy testing was performed by checkerboard micro dilution method and validation of different checkerboard ratios by static and dynamic time-kill analysis and in vitro pharmacokinetic/pharmacodynamics (PK/PD) model, and semi mechanistic PK/PD modeling was used to calculate and validate the synergistic effect of drug combination. Both checkerboard and static time-kill assays demonstrated the greater synergistic effect (FICI=0.37) of the aditoprim (MIC=0.25 ug/ml)-sulfamethoxazole (MIC=>64 ug/ml) combination against all T. Pyogenes isolates. In the in vitro PK/PD model, the dosage proportion of sulfamethoxazole 4 mg/ml twice a day in combination of steady-state aditoprim 1 mg/ml efficiently repressed growth of bacteria in 24 hours with the ratio of 2-log10 decrease, related to the early inoculum against three T. Pyogenes isolates. The semi mechanistic PK/PD model projected that a combination of high dose of aditoprim (2 mg/ml) with sulfamethoxazole (2 mg/day) was necessary to attain the killing of bacteria below the detection limit (_LOD; i.e., 1 log10CFU/ml) at 24 hr with an MIC (SMZ) of 64 ug/ml. However, it is anticipated that a combination of high dose of aditoprim with sulfamethoxazole is critical to attain the suppressed bacterial growth to